2020
DOI: 10.52442/jrmi.v6i1.198
|View full text |Cite
|
Sign up to set email alerts
|

Residential status of medical students as a factor affecting formative and summative academic performance in Forensic Medicine at Rehman Medical College, Peshawar, Pakistan

Abstract: Introduction: A rigorous characterization of the impact of residential status of medical students (hostelites vs. day scholars) on the particulars of their academic performance has been lacking in Pakistan. Objective: To determine the relation of residential status of third year MBBS students to their academic performance in Forensic Medicine based on comparison of their pre-professional and professional examinations results during 2019. Materials & Methods: A comparative study was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…22 Rehman K et al reported no difference of academic performance in medical professional exam but day scholars were found to be better than their other counterparts. 23,24 The country's education system needs to identify all the possible barriers while inculcating a change in the thinking style, research, deepening critical thinking, and also a change in teachers' attitudes toward curriculum designing (goals, objectives, learning content, instructional designs and evaluation methods); more so, it is suggested that proper attention should be paid to the need to develop and utilize critical thinking skills in the learners' education. 25 The current study results suggest that medical curriculum should be taught in an integrated manner to stimulate critical thinking skills among future healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…22 Rehman K et al reported no difference of academic performance in medical professional exam but day scholars were found to be better than their other counterparts. 23,24 The country's education system needs to identify all the possible barriers while inculcating a change in the thinking style, research, deepening critical thinking, and also a change in teachers' attitudes toward curriculum designing (goals, objectives, learning content, instructional designs and evaluation methods); more so, it is suggested that proper attention should be paid to the need to develop and utilize critical thinking skills in the learners' education. 25 The current study results suggest that medical curriculum should be taught in an integrated manner to stimulate critical thinking skills among future healthcare providers.…”
Section: Discussionmentioning
confidence: 99%